Waqf and Poverty: A Review - Aam (SMART Insight, 2021)
The existence of waqf in Islam in addition to getting the pleasure and reward of Allah, is also a social service to humans. The form of waqf in social worship is in the form of community empowerment, social security, health, education, agriculture, animal husbandry, and others. This concept indicates that Islam has thought of a solution to the problem of social inequality in society. This bibliometric study maps out research related to the development of research trends themed Waqf & Poverty during the period 2002-2021 from 49 published journal sources. Descriptive statistical methods were used, and bibliometric analysis was performed using the VOSViewer application to determine the bibliometric map. The number of articles discussing the theme of Waqf & Poverty shows an increasing trend from year to year, in line with the development of Islamic finance. The most popular keywords used are Waqf, poverty and cash waqf. The most prolific writers were Muhammad A.D., Haneef M.A., and Mohammed M.O. Meanwhile, the country with the most popular writers and the most is Malaysia. The research provides information for researchers who focus on research in the field of Islamic Social Finance. In the end, this theme has the potential to continue to be developed.